The use of by-products of wine-making in creating functional confectionery - Kalinovska, Tatyana; Obolkina, Vera (My University, 2013)
The thesis is aimed at studying the concentration of pectin and phenol substances in grapes and in processed grapes products as well as at assessing the expediency of making them part of recipe as a valuable raw material for new kinds of confectionery.
Keywords: виноградні вичавки; виноградні кісточки; протопектин; кафедра технології хлібопекарських і кондитерських виробів